ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2012-2014) - Yodhi Yustar Affif Tjokrowardojo, 11.05.52.0008; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2017)
This study aimed to examine the analysis of factors influencing the dividend policy.This study is performed to examine the effect of Liquidity, Leverage, Growth, Owner Institute and Profitability toward Dividend Payout Ratio (DPR) in manufacture companies that is listed in Indonesian Stock Exchange over period 2012-2014. The data is obtained based on Indonesian Capital Market Directory (ICMD) and Financial Reportfrom Indonesia Stock Exchange (BEI) period 2012-2014. The population in this study are 155 companies listed in Indonesia Stock Exchange in 2012-2014. The sample selection was conducted using purposive sampling of 140 companies. Data testing technique is to use multiple linear regression analysis. The analysis showed that the variables Liquidity, Growth, and Profitability positive effect on dividend policy. While the Leverage, and Owner Institute negative effect on dividend policy.Keywords: Liquidity, Leverage, Growth, Owner Institute, Profitability and Dividend Payout Ratio (DPR)